Effect of synthesis time on plasmonic properties of Ag dendritic nanoforests. (2022) - Huang, Hung Ji; Chang, Han-Wei; Lee, Chia-Yen; Shiao, Ming-Hua; Chiu, Yen-Ling; Lee, Pee-Yew; Lin, Yung-Sheng
No abstract available